Die ensiklopediese plek van Bybelkunde - Engelbrecht, J. J. (Hervormde teologiese studies, 1987)
The encyclopedic place of Biblical StudiesIs Biblical Studies part of theology, or has theology lost its grip on Biblical Studies, as it has lost its grip on Geology and Palaeontology as early as one and a half century ago?Is it possible to distinguish between different levels of Biblical study, some levels dealing with essentially theological questions and others with more general questions of a historical, archaeological, literary or linguistic nature?What is and should be the relationship between the Departments of Biblical Studies on the one hand, and the Departments of Old Testament and New Testament on the other hand?